The conditions of socioeconomic development exploring the legitimacy of social norms, trust, and corruption in Chile and Argentina - Daniel Míguez; Matías Dewey (Max Planck Institute for the Study of Societies, 2018)
A growing body of research, based on large-scale international comparisons, has associated socioeconomic development with several intervening factors, such as levels of respect for social norms, interpersonal trust, degrees of confidence in public institutions, or incidence of corruption in governmental bodies. The paper contributes to this body of scholarship by comparing the differing socioeconomic development experienced by Chile and Argentina between 1983 and 2013. Specifically, the paper inquires whether the greater socioeconomic development experienced by Chile was actually related to greater legitimacy of the law, higher levels of trust in public institutions, lower perceived levels of corruption, and greater interpersonal trust. The results of our exploration do not completely confirm or disprove this thesis. Instead, they reveal not only the need for a nuanced approach to how these factors relate to socioeconomic progress but also for their forms of association to be considered in the context of politically, socially, and economically fluctuating conditions. – – Eine zunehmende Anzahl von Forschungsarbeiten basierend auf großen internationalen Vergleichsstudien weist einen Zusammenhang zwischen sozioökonomischer Entwicklung und verschiedenen Einflussfaktoren auf. Beispielsweise spielen das Ausmaß von Respekt für soziale Normen, interpersonelles Vertrauen, der Grad des Vertrauens in behördliche Einrichtungen oder die Auswirkungen von Korruption in staatlichen Institutionen eine Rolle. Als Beitrag zu dieser Forschung vergleicht das Papier die unterschiedlichen sozioökonomischen Entwicklungen in Chile und Argentinien zwischen 1983 und 2013. Im Vordergrund steht die Frage, ob die größere sozioökonomische Entwicklung, die in Chile stattgefunden hat, tatsächlich mit einer höheren Legitimität der Gesetzgebung, größerem Vertrauen in öffentliche Institutionen, niedrigerem wahrgenommenen Korruptionsgrad und größerem interpersonellen Vertrauen in Zusammenhang zu setzen ist. Diese These wird von den Ergebnissen der vorliegenden Studie weder eindeutig bestätigt noch widerlegt. Stattdessen legen sie die Notwendigkeit nahe, mit einem differenzierten Ansatz zu untersuchen, wie diese Faktoren sich auf sozioökonomischen Fortschritt auswirken und wie ihre Assoziierungen im Kontext politisch, sozial und ökonomisch fluktuierender Rahmenbedingungen zu berücksichtigen sind.
hdl:21.11116/0000-0002-6C8B-9
Keywords: 300; Argentina; Chile; corruption; development; fiscal policy; norms; trust; Argentinien; Entwicklung; Korruption; Normen; Steuerpolitik; Vertrauen